Meningkatkan Respons Bencana: Analisis Kualitas Pelayanan Di Suku Dinas Sosial Jakarta Selatan - Muh. Mashuri Masyhuda; A. Fauzan Fadlan; Nazifah Husainah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background - The low quality of service in disaster management is caused by the lack of work skills training by service officers, limited communication and slow delivery of information to the public regarding disaster management and the ability of service officers in conveying information effectively in disaster situations. The ability of service officers to understand the work carried out from the formal education side can also support disaster management, while service officers from formal education are still low, especially those with Bachelor's degrees. In addition, the less friendly work attitude of service officers in providing services to the public is an important concern for the Agency. Therefore, service officers can make efforts to improve their abilities through these factors so that they can achieve an increase in the quality of service in the field of disaster management. Aim - The purpose of this study is to conduct an analysis of the factors that influence the quality of services in disaster management at the Social Service Sub-dept. of South Jakarta Administrative City related to the skills, communication, education level and work attitude of service officers. Design/Methodology/Approach - This study uses quantitative methods. Data sources from primary data and secondary data. Data collection techniques using questionnaire methods and interviews. The population in this study were 126 members of Tagana South Jakarta City using a simple random sampling method. Data analysis techniques were carried out through correlation tests, determination tests, hit t and F tests and multiple linear regression tests. Findings - The results of the analysis show that the skill factor has a positive and significant effect on the quality of disaster management services at the South Jakarta City Social Service Sub-dept., the communication factor has a positive and insignificant effect on the quality of disaster management services at the South Jakarta City Social Service Sub-dept., the education level factor has a positive and significant effect on the quality of disaster management services at the South Jakarta City Social Service Sub-dept., the work attitude factor has a positive and significant effect on the quality of disaster management services at the South Jakarta City Social Service Sub-dept. Implications - This study emphasizes the importance of improving the quality of disaster management services influenced by skills, communication, education level and work attitude factors. Agencies are expected to provide capacity building to Tagana members, both from training related to work skills, communication, work attitudes and encouraging service officers to improve formal education, by considering the needs of agencies in implementing disaster management service programs in the community. Research Limitations - The limitations of this study only include respondents who are Tagana members in the South Jakarta area. And the independent variables studied are only related to skills, communication, education level and work attitude while the dependent variable is service quality.